1996
DOI: 10.1007/bf00119732
|View full text |Cite
|
Sign up to set email alerts
|

A quantitative technique for comparing synthetic porous hydroxyapatite structures and cancellous bone

Abstract: There are many different materials currently available for cancellous bone grafting. There is however, very little information relating the morphology of these materials to cancellous bone. Work was undertaken to develop a quantitative method for comparing synthetic hydroxyapatite bone structures with cancellous bone. The bases for comparison were mean plate thickness, mean plate distance, mineral area fraction, mineral volume fraction and plate orientation coupled with mechanical tests. The aim of this work w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 28 publications
2
15
0
Order By: Relevance
“…This approached the reported flexural strength of 2-11 MPa for sintered porous hydroxyapatite implants [4] and a tensile strength of 3.5 MPa for cancellous bone [50]. Cancellous bone had an elastic modulus of about 0.30 GPa [51], compared to about 1 GPa for the injectable CPC scaffold (Fig. 6).…”
Section: Article In Presssupporting
confidence: 55%
“…This approached the reported flexural strength of 2-11 MPa for sintered porous hydroxyapatite implants [4] and a tensile strength of 3.5 MPa for cancellous bone [50]. Cancellous bone had an elastic modulus of about 0.30 GPa [51], compared to about 1 GPa for the injectable CPC scaffold (Fig. 6).…”
Section: Article In Presssupporting
confidence: 55%
“…In the present study, the macroporous CPC scaffold had a strength of about 4 MPa, matching the reported 3.5 MPa for cancellous bone [38]. Macroporous CPC had elastic modulus of about 500 to 1000 MPa, which compares with the reported elastic modulus of approximately 300 MPa for cancellous bone [39]. A literature search did not found the work-of-fracture value of cancellous bone.…”
Section: Discussionsupporting
confidence: 80%
“…34,39 Cortical bone has a reported flexural elastic modulus of about 12.8 GPa, 40 and cancellous bone has an elastic modulus of about 0.30 GPa. 41 The cement with suture and chitosan developed in the present study possessed an elastic modulus of 3.2 GPa at 1 day and 3.0 GPa at 35 days, within the range for cortical bone and cancellous bone.…”
Section: Discussionmentioning
confidence: 95%